Cysteine Cathepsins and Cystatins as Cancer Biomarkers - Lah, Tamara T.; Obermajer, Nataša; Alonso, María Beatriz Durán; Kos, Janko (The Cancer Degradome, 2008)
Cysteine cathepsins are lysosomal cysteine proteases that are involved in a number of important biological processes, including intracellular protein turnover, propeptide and prohormone processing, apoptosis, bone remodelling, and reproduction. In cancer, the cathepsins have been linked to extracellular matrix remodelling and to the promotion of tumour cell motility, invasion, angiogenesis and metastasis, resulting in poor outcome of the disease. The levels of cathepsins as well as of their endogenous inhibitor cystatins in clinical samples have been suggested as potential biomarkers, and this chapter is focused on their role to predict the diagnosis, risk of recurrence and death, and response to therapy in patients with cancer.